Log-periodic monopole array with uniform spacing and uniform height - Song, Qinghua (2020)
This paper presents a log-periodic monopole array (LPMA) with uniform spacing and uniform height operating in a wideband of 2-6 GHz. Different from the conventional LPMA with logarithmic spacing and height, the proposed antenna with uniform spacing and uniform height simplifies the design procedure and retains a low profile. The top-hat monopoles and folded top-hat monopoles are used to reduce the height of the antenna. A maximum bandwidth of 3:1 is theoretically proposed by considering the maximum and minimum spacing factor of the array. A meandering microstrip line is employed as the feeding line. The compensation of the length of the feeding line is proposed for the uniformly spaced LPMA compared to the conventional array. A prototype is fabricated and tested. Measured results indicate that an impedance bandwidth from 2 to 6 GHz (3:1) with VSWR < 2 is achieved. The measured peak realized gain is in the range of 6.6-8.7 dBi, which has great potential in many communication systems such as missile and airborne applications.